The Influence of the Health Belief Model on the Risk Factors of Dengue Fever Occurrence in the Working Area of Sei Suka Public Health Center, Batubara Regency 2025 - Maharani, Usti; Donal Nababan; Henny Arwina Bangun; Jasmen Manurung (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
In the prevention of dengue fever risk, the Health Belief Model can be a useful tool to understand how the public's perceptions and attitudes towards prevention efforts affect the risk of dengue fever occurrence. The objective of this study is to analyze the influence of the Health Belief Model on the risk factors for dengue fever occurrence in the working area of Sei Suka Public Health Center, Batubara Regency, in 2025. This research is descriptive-analytic with a cross-sectional study design. The research period will be from July 2024 to January 2025. The sample consists of 100 heads of households. Bivariate data analysis will use the Chi-square test, and multivariate analysis will employ logistic regression. The results of the bivariate analysis show a relationship between perceived susceptibility (p=0.010), perceived severity (p=0.001), perceived benefits (p=0.000), perceived barriers (p=0.001), and cues to action (p=0.000) with the risk of dengue fever occurrence in the working area of Sei Suka Public Health Center, Batubara Regency. The dominant factor affecting the risk of dengue fever in the working area of Sei Suka Public Health Center, Batubara Regency, is the cues to action factor, with a B value of 1.609 and a p-value of 0.000.